Geographic information 1994 : (Taylor and Francis, 1993)
This book includes coverage of the current issues, themes, technology and developments associated with the rapidly growing world of geographic information systems. Now includes a new glossary of GIS terms, a comprehensive directory of GIS services and expert reviews of GIS initiatives and applications.